2018
DOI: 10.1371/journal.pone.0206888
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a preconception lifestyle intervention in obese infertile women on diet and physical activity; A secondary analysis of a randomized controlled trial

Abstract: BackgroundLifestyle changes are notoriously difficult. Since women who intend to become pregnant are more susceptible to lifestyle advice, interventions during this time window might be more effective than interventions during any other period in life. We here report the effects of the first large preconception lifestyle intervention RCT on diet and physical activity in obese infertile women.MethodsIn total, 577 women were randomized between a six-month lifestyle intervention program (intervention group; N = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…While many studies have explored weight maintenance in pregnant women, focused primarily on limiting gestational weight gain, few have targeted the vital preconception phase [ 12 , 24 ]. Women who intend to become pregnant are more amenable to lifestyle advice, so interventions during this time may be more effective than during any other period in life [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have explored weight maintenance in pregnant women, focused primarily on limiting gestational weight gain, few have targeted the vital preconception phase [ 12 , 24 ]. Women who intend to become pregnant are more amenable to lifestyle advice, so interventions during this time may be more effective than during any other period in life [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle interventions of >12 months duration showed more consistent weight loss results compared to interventions of <6 months duration (Naslund et al, 2017). We have shown that a lifestyle intervention, offered during the preconception period when women are particularly receptive to lifestyle advice (McBride, Emmons, & Lipkus, 2003), is effective in improving lifestyle (van Elten et al, 2018), reducing body weight and improving cardiometabolic health (van Dammen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional status of women before conception can affect the critical development process during pregnancy and child born. In addition, women who intend to become pregnant are more vulnerable to suggestions for lifestyle changes [3].…”
Section: Introductionmentioning
confidence: 99%